The Influence of Halal Labeling, Promotion, Product Quality, and Brand Image on Purchasing Decisions for Teh Pucuk Harum - Wildan, Tafrikhul; Justiana Astuti, Herni; Widyaningtyas, Dian; Endratno, Hermin (Asian Journal of Management Analytics, 2025)
This study aims to identify the factors that affect the purchase decision of teh pucuk harum products. The research uses a quantitative method by collecting primary data through a survey of 108 respondents who are active students from UNSOED, UMP, and UIN Purwokerto. Data were analyzed using IBM SPSS Statistics 26. The results of the study show that halal labeling has a negative effect on purchase decisions, because consumers already consider the product halal without looking at the label. Promotion does not have a significant effect because the promotional strategy has not attracted enough interest from consumers. On the other hand, product quality and brand image have a positive effect, as consumers consider taste and brand reputation more in making purchasing decisions.